Oral administration of 5-hydroxytryptophan (5-HTP) impairs decision making under ambiguity but not under risk: evidence from the Iowa Gambling Task - Gendle, Mathew H.; Golding, Abbe C. (Human psychopharmacology, 2010)
Objective Although the serotonin precursor 5‐hydroxytryptophan (5‐HTP) is marketed as a psychoactive nutritional supplement, knowledge is limited regarding the effects of exogenous 5‐HTP on brain activity. This study examined if oral administration of 5‐HTP to healthy adults impacted: (1) mood states, as measured by the Profile of Mood States (POMS); and (2) performance on the Iowa Gambling Task (IGT), a measure sensitive to alterations in frontocortical serotonin levels. Methods A sample of 46 undergraduates participated, and each received either two 50 mg 5‐HTP capsules or placebos, and completed the IGT and POMS following an absorption period. Results 5‐HTP did not significantly alter mood states, but did impair performance on the IGT. Specifically, the 5‐HTP group performed more poorly than the placebo group during the first 20 trials of the IGT but did not differ from the placebo group on trials 21–100. This suggests that oral 5‐HTP specifically impaired decision making under ambiguity but not under risk. Males also performed more poorly on the first 20 trials of the IGT, regardless of treatment group. Conclusions Oral 5‐HTP is psychoactive at low doses. Decisions made under ambiguity may be differentially sensitive to increased serotonin release or associated reductions in frontocortical dopamine activity. Copyright © 2010 John Wiley & Sons, Ltd.